Despicable me - Paul, Cinco; Daurio, Ken.; Meledandri, Chris; Healy, Janet; Cohen, John.; Renaud, Chris; Coffin, Pierre; Segel, Jason, 1979-; Brand, Russell, 1975-; Carell, Steve, 1963-; Arnett, Will.; Wiig, Kristen, 1973-; et al. (Universal City, Calif. : Universal Studios Home Entertainment, 2010)
Gru delights in all things wicked. Surrounded by an army of tireless little yellow minions, and armed with his arsenal of shrink rays, freeze rays, and battle-ready vehicles for land and air, he vanquishes all who stand in his way. Until the day he encounters the immense will of three little orphaned girls who look at him and see something that no one else has ever seen, a potential dad.
Title from disc surface.
Based on a story by Sergio Pablos.
Special features: the world of Despicable me, featurette; despicable beats; Gru's rocket builder.
Original songs and themes by Pharrell Williams ; score by Pharrell Williams, Heitor Pereira ; editors, Pamela Ziegenhagen-Shefland, Gregory Perler.
Voices: Jason Segel, Russell Brand, Steve Carell, Kristen Wiig, Will Arnett, Julie Andrews, Miranda Cosgrove, Danny McBride, Jack McBrayer.
MPAA rating: PG; for rude humor and mild action.
Keywords: Supervillains -- Juvenile drama; Orphans -- Juvenile drama; Feature films; Children's films; Comedy films; Animated films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities